Low velocity impact analysis of pineapple leaf/kenaf fibre-reinforced vinyl ester hybrid composites for structural applications - Mazlan, Ali Ahmad (2021)
Recently, all the government legislation as well as environmental consciousness has enforced the industrial and academic researchers to produce eco-friendly, lightweight and renewable composite materials. The study of natural plant fibres (pineapple, kenaf etc.) as reinforcement in polymer matrix has rose rapidly due to their unique properties such as low in cost, biodegradable and renewable. Pineapple leaf fibre (PALF) and kenaf fibres (KF) are one of the natural fibres that being widely used as a reinforcement in the polymer matrix composites. Vinyl ester (VE) resin was used as a matrix in this research work. The present research works investigated the effect of fibre length of PALF (short, mixed and long), the effect of fibre orientation angle of woven KF on the tensile and flexural properties of PALF/VE composites. This research work also investigated the low velocity impact (LVI) and compression after impact (CAI) properties. Besides mechanical testing, thermal testing such as thermogravimetric analysis (TGA) and dynamic mechanical analysis (DMA) were also conducted. The composites with long (30 mm) fibres were chosen to be hybridized with woven KF (PALF/KF/VE hybrid composites) for further investigation which varying the fibre orientation angle of KF (0°/90°, 30°, 45° and 60°). The hybrid composites were fabricated with five layers (2KF/PALF/2KF) by using the hand lay-up technique. As a result, the hybrid composites with 0°/90° orientation showed the optimum mechanical properties and was chosen to be tested further with the LVI with different level of energy (5 J, 10 J and 15 J) and CAI testing. From the LVI testing, the hybrid composites can hold up to 15 J of impact energy. CAI results showed that the hybrid composites impacted with 5 J gave the optimum value of compressive strength than 10 J and 15 J. TGA and DMA testing showed that the incorporation of fibres in the matrix enhance the thermal stability of the composites.